2009
DOI: 10.1080/03079450902912143
|View full text |Cite
|
Sign up to set email alerts
|

Identification of iron-acquisition proteins ofAvibacterium paragallinarum

Abstract: When Avibacterium paragallinarum reference strain 0083 (serovar A) was grown in an iron-restricted culture medium, the expression of the 60, 68 and 93 kDa outer membrane proteins increased as compared with normal media. Sera of chickens experimentally infected with Av. paragallinarum recognized these ironrestriction induced proteins, suggesting their expression in vivo. The three outer membrane proteins were identified as transferrin receptor and iron transport proteins by mass spectroscopy and a search in seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As previously reported, perhaps reduction of global gene expression and induction of unique genes are also helpful for A. paragallinarum to enter stationary phase by ceasing growth and retaining survivability for a long time (Miksch and Dobrowolski, 1995). Notably, several upregulated genes are demonstrated to be able to facilitate A. paragallinarum to effectively obtain iron for their growth (Abascal et al, 2009). In our study, when bacteria are in an ironrestriction environment, these upregulated gene products that we found can also be helpful for the release of iron from iron-binding proteins and compounds, promoting the acquisition and use of more iron sources by bacteria.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As previously reported, perhaps reduction of global gene expression and induction of unique genes are also helpful for A. paragallinarum to enter stationary phase by ceasing growth and retaining survivability for a long time (Miksch and Dobrowolski, 1995). Notably, several upregulated genes are demonstrated to be able to facilitate A. paragallinarum to effectively obtain iron for their growth (Abascal et al, 2009). In our study, when bacteria are in an ironrestriction environment, these upregulated gene products that we found can also be helpful for the release of iron from iron-binding proteins and compounds, promoting the acquisition and use of more iron sources by bacteria.…”
Section: Discussionmentioning
confidence: 60%
“…The siderophore transport system, which is capable of acquiring free inorganic iron, consists of both siderophores and TonB-dependent transferrin receptors (TBDR) on the outer membrane of bacteria (Chu et al, 2010). In A. paragallinarum, Abascal et al (2009) have identified three upexpressed outer membrane proteins acting as transferrin receptor and iron transport proteins in bacteria cultured in iron-restricted medium, which are regulated by the Fur protein (Abascal et al, 2009). They speculate that these proteins are associated with the colonization of bacteria in an iron-limited host environment.…”
Section: Introductionmentioning
confidence: 99%
“…TonB-dependent transporters (TBDTs) are membrane proteins that have high affinity for iron, vitamin B 12 , siderophores and carbohydrates, which are important for bacteria. Iron is the main substrate for TBDTs, and it participates in many bacterial metabolic processes [7].…”
Section: Introductionmentioning
confidence: 99%